Elite cassava clones (Manihot esculenta) grown in Zambia: effects of drying techniques on their chemical, functional, and pasting properties - Alamu, Emmanuel Oladeji; Manda, N.; Ntawuruhunga, P.; Abass, A.; Maziya-Dixon, Busie (Frontiers Media, 2023)
Introduction: Cassava (Manihot esculanta) is becoming an important crop in most developing countries, especially Zambia. However, cassava roots deteriorate quickly after harvest, producing flour or chips of sub-optimal quality. Hence the evaluation of processing procedures to extend the product’s shelf-life cannot be overemphasized. This study investigated the effects of different drying methods on the chemical, functional and pasting properties of selected advanced cassava clones grown in Zambia. Methods: Fresh Roots of the seven cassava clones (harvested 12 months after planting) were sampled, peeled, washed and dried using the three drying methods (sun-drying, oven-drying and freeze-drying). The flour samples from these drying methods were analyzed using standard laboratory methods for primary chemical, functional and pasting properties. The data generated were statistically analyzed for descriptive, analysis of variance (ANOVA), and the means were separated at p< 0.05. Results and discussion: The clone and drying method had significant effects (p < 0.001) on most chemical, functional and pasting properties. Clone 00/0093 had consistently lower 1E∗ values for each drying method than other clones. The overall mean of total color difference (1E∗) across the genotypes revealed the ranking 1E∗ for drying techniques in the order of oven > sun > freeze drying. Generally, the highest sugar content was recorded for the freeze-dried samples. Similarly, the total starch content was higher in the sun-dried samples of six out of the seven samples than in the oven-dried samples. The functional properties ranged from 31.29–61.04%, 2.31–5.41%, 119.68–206.78% and 54–70 for solubility, swelling power, water absorption capacity and dispersibility, respectively. Conclusion: In conclusion, the clonal effect of the cassava and drying method significantly affected the cassava flours’ color, chemical, functional, and pasting properties.